2010
DOI: 10.1007/s10509-009-0254-9
|View full text |Cite
|
Sign up to set email alerts
|

de Sitter expansion with anisotropic fluid in Bianchi type-I space-time

Abstract: Some features of the Bianchi type-I universes in the presence of a fluid that wields an anisotropic equation of state (EoS) parameter are discussed in the context of general relativity. The models that exhibit de Sitter volumetric expansion due to the constant effective energy density (the sum of the energy density of the fluid and the anisotropy energy density) are of particular interest. We also introduce two locally rotationally symmetric models, which exhibit de Sitter volumetric expansion in the presence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…In literature, many authors have considered totally anisotropic Bianchi-I space-times with only two skewness parameters of DE [39,40]. Finally, we assume that ω = const.…”
Section: Solution Of the Field Equationsmentioning
confidence: 99%
“…In literature, many authors have considered totally anisotropic Bianchi-I space-times with only two skewness parameters of DE [39,40]. Finally, we assume that ω = const.…”
Section: Solution Of the Field Equationsmentioning
confidence: 99%
“…Mota (2008a, 2008b) have investigated cosmological models with anisotropic EoS and have also shown that the present SN Ia data allows large anisotropy. Recently, Akarsu and Kilinc (2010c) have described some features of the Bianchi type-I universes in presence of fluid that wields an anisotropic EoS. Hence, for a realistic cosmological model one should consider spatially homogeneous and anisotropic space-times and then show whether they can evolve to the observed amount of homogeneity and isotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Following, Akarsu and Kilinc [37,38,50] and Yadav [21], we split the conservation of energy momentum tensor of the DE into two parts, one corresponds to deviations of EoS parameter and other is the deviation-free part of T (de)ij ;j = 0:…”
Section: Solution Of the Field Equations And Its Physical Significancementioning
confidence: 99%